Theoretical model for predicting uniaxial stress-strain relation by dual conical indentation based on equivalent energy principle - Chen, Hui; Cai, Li-xun (Acta materialia, 2016)
For conical indentation, the strain energy is a function of the semi-vertical cone angle, the indentation depth and the stress-strain relation. According to equivalent energy principle of representative volume elements (RVE) and the classical cavity assumption for material deformation region, the function with dual-parameters about volume and deformation is theoretically derived in the present study. This original equivalent-energy indentation model (EIM) is capable of forward-predicting load-depth relation and reverse-predicting uniaxial stress-strain relation for ductile materials only based on loading part of indentation. Further analyses show that the forward and reverse predicted results from EIM method are in excellent agreement with those by finite element analyses (FEA). Macro conical indentation experiments on five types of metals have been conducted using conventional indenters which are similar to Rockwell sclerometer. Consequently, the stress-strain relations predicted by EIM are quite close to those from standard tensile tests. [Display omitted]